Natural attenuation of arsenic in the wetland system around abandoned mining area - An, J.; Kim, J.Y.; Kim, K.W.; Park, J.Y.; Lee, J.S.; Jang, M. (2011)
Mechanisms of natural attenuation of arsenic (As) by wetland plants may be classified by plant uptake and adsorption and/or co-precipitation by iron (oxy)hydroxide formed on the root surface of plants or in rhizosediment. A natural Cattail (Typha spp.) wetland impacted by tailings containing high levels of As from the Myungbong abandoned Au Mine, South Korea was selected, and the practical capability of this wetland to attenuate As was evaluated. The As concentrations in the plant tissues from the study wetland were several-fold higher than those from control wetland. SEM-EDX analyses demonstrated that iron plaques exist on the rhizome surface. Moreover, relatively high As contents bonded with hydrous iron oxides were found in the rhizosediments rather than in the bulk sediments. It was revealed through the leaching and sequential extraction analyses that As existed as more stable forms in the wetland sediment compared with adjacent paddy soil, which is also contaminated with As due to input of mine tailings. The As concentration ratios of extracted solution to sediment/soil represented that the wetland sediment showed significant lower values (10-fold) rather than the paddy soil with indicating high As stability. Also, As in the wetland sediment was predominantly bonded with residual phases on the basis of results from sequential extraction analysis. From these results, it is concluded that transformation of As contaminated agricultural field to wetland environment may be helpful for natural attenuation until active remediation action. Â© 2010 Springer Science+Business Media B.V.